Aggregation behavior of the amyloid model peptide NACore. (2019) - Pallbo, Jon; Sparr, Emma; Olsson, Ulf
Abstract: The aggregation of the 11 residue long NACore peptide segment of α -synuclein (68-GAVVTGVTAVA-78) has been investigated using a combination of cryogenic transmission electron microscopy (cryo-TEM), small- and wide-angle X-ray scattering, and spectroscopy techniques. The aqueous peptide solubility is pH dependent, and aggregation was triggered by a pH quench from pH 11.3 to approximately pH 8 or 6, where the average peptide net charge is weakly negative (pH 8), or essentially zero (pH 6). Cryo-TEM shows the presence of long and stiff fibrillar aggregates at both pH, that are built up from β -sheets, as demonstrated by circular dichroism spectroscopy and thioflavin T fluorescence. The fibrils are crystalline, with a wide angle X-ray diffraction pattern that is consistent with a previously determined crystal structure of NACore. Of particular note is the cryo-TEM observation of small globular shaped aggregates, of the order of a few nanometers in size, adsorbed onto the surface of already formed fibrils at pH 6. The fibrillation kinetics is slow, and occurs on the time scale of days. Similarly slow kinetics is observed at both pH, but slightly slower at pH 6, even though the peptide solubility is here expected to be lower. The observation of the small globular shaped aggregates, together with the associated kinetics, could be highly relevant in relation to mechanisms of secondary nucleation and oligomer formation in amyloid systems.